Biochemical Characterization of 3-Methyl-4-nitrophenol Degradation in Burkholderia sp. Strain SJ98 - Min, Jun; Lu, Yang; Hu, Xiaoke; Zhou, Ning-Yi (Frontiers in Microbiology, 2016)
Several strains have been reported to grow on 3-methyl-4-nitrophenol (3M4NP), the primary breakdown product of the excessively used insecticide fenitrothion. However, the microbial degradation of 3M4NP at molecular and biochemical levels remains unknown. Here, methyl-1,4-benzoquinone (MBQ) and methylhydroquinone (MHQ)，rather than catechol proposed previously, were identified as the intermediates before ring cleavage during 3M4NP degradation by Burkholderia sp. strain SJ98. Real-time quantitative PCR analysis indicated that the pnpABA1CDEF cluster involved in para-nitrophenol (PNP) and 2-chloro-4-nitrophenol (2C4NP) catabolism was also likely responsible for 3M4NP degradation in this strain. Purified PNP 4-monooxygenase (PnpA) is able to catalyze the monooxygenation of 3M4NP to MBQ and exhibited an apparent Km value of 20.3±2.54 μM for 3M4NP, and pnpA is absolutely necessary for the catabolism of 3M4NP by gene knock-out and complementation. PnpB, a 1,4-benzoquinone reductase catalyzes the reduction of MBQ to MHQ, and also found to enhance PnpA activity in vitro in the conversion of 3M4NP to MBQ. By sequential catalysis assays, PnpCD, PnpE and PnpF were likely involved in the lower pathway of 3M4NP catabolism. Although NpcCD, NpcE and NpcF are able to catalyze the sequential conversion of MHQ in vitro, these enzymes are unlikely involved in 3M4NP catabolism because their coding genes were not upregulated by 3M4NP induction in vivo. These results revealed that the enzymes involved in PNP and 2C4NP catabolism were also responsible for 3M4NP degradation in strain SJ98. This fills a gap in our understanding of the microbial degradation of 3M4NP at molecular and biochemical levels and also provides another example to illustrate the adaptive flexibility in microbial catabolism for structurally similar compounds.